KONTRAK KERJA BERBASIS KINERJA DAN EVALUASI PENERAPAN PADA JALAN NASIONAL - Tamin, Rizal Z.; Tamin, Adriananda Z.; Marzuki, Puti F. (Jurnal HPJI, 2016)
Abstract Performance Based Contract is an innovation maintenance contract to improve the quality and value-added of the national road service. Under this contract, the performance of contractors is not evaluated by the input and processes, but by the output and outcome performance indicators which had already clearly been defined and measurable. Contractors are free to establish what, when, how, and where the maintenance work is performed. With its creativity and innovation, the contractor can increase the added value of maintenance work to more directly meet the road user expectations. Since 2011 the Directorate General of Highways has been trying to implement the Performance Based Contract, but the condition of the national road service is not ideal yet, characterized by the frequent of overloading, the provisions of program development and preservation are not yet firm, the design life, road damage, and construction failure that have not been applied resulting in the need for adjustment to the initial concept of the Performance Based Contract. This paper discusses the adjustments made, the deviation of the basic concepts of the Performance Based Contract, analysis of the problems faced, and the challenges to be overcome to enhance the concept of the Performance Based Contract for national road maintenance in the future. Keywords: Performance Based Contract, National Road, overloading, road maintenance  Abstrak Performance Based Contract (PBC) merupakan kontrak inovasi pemeliharaan untuk meningkatkan mutu dan nilai tambah penyelenggaraan jalan nasional. Dalam kontrak ini, kinerja pemeliharaan kontraktor tidak dinilai dari input dan proses, tetapi melalui indikator kinerja output dan outcome yang telah lebih dulu didefinisikan dengan jelas dan terukur. Kontraktor bebas menetapkan apa, kapan, bagaimana, dan di mana pekerjaan pemeliharan dilakukan. Dengan kreativitas dan inovasinya, kontraktor dapat meningkatkan nilai tambah pekerjaan pemeliharaan untuk lebih langsung memenuhi harapan pengguna jalan. Ditjen Bina Marga semenjak tahun 2011 telah melakukan uji coba penerapan PBC, namun kondisi penyelenggaraan jalan nasional yang belum ideal ditandai oleh seringnya beban berlebih, ketentuan program pembangunan dan preservasi yang belum tegas, umur perencanaan, kerusakan, serta kegagalan bangunan yang belum diterapkan mengakibatkan perlunya dilakukan penyesuaian terhadap konsep initial PBC. Makalah ini membahas penyesuaian yang dilakukan, penyimpangannya terhadap konsep dasar PBC, analisis terhadap permasalahan yang dihadapi, dan tantangan yang masih harus diatasi untuk mengembangkan konsep PBC pemeliharaan jalan nasional di masa yang akan datang. Kata-kata kunci: Performance Based Contract, jalan nasional, beban berlebih, pemeliharaan jalan